Physicians' Opinion Regarding Extended Access to Hormonal Contraception in Switzerland - Tamara Yous; Samuel Allemann; Monika Lutters (MDPI AG, 2021)
(1) Background: Access to hormonal contraceptives (HC) strongly differs between countries and varies from over the counter (OTC) to prescription-only availability. This study aimed to identify opinions among physicians in Switzerland regarding extended access to HC. (2) Methods: Web-based survey among physicians (gynecologists, general practitioners, and pediatricians) in Switzerland. (3) Results: Hundred sixty-three physicians, mainly gynecologists, participated in this survey and 147 (90%) were included for analysis. A total of 68% (n = 100) answered that prescription-only status could be extended under certain conditions but physicians were concerned about patients' safety (97%, n = 142). Moreover, there was concern about insufficient patient education on HC (93%, n = 136) and that women may forego preventive examinations (80%, n = 118). Participants did not support OTC availability (93%, n = 136). Pharmacists prescribing (including initiation of HC) revealed controversial results, but a combined access model (initial prescription from physician and follow-up prescriptions by pharmacists) found acceptance in 70% (n = 103). (4) Conclusions: Participating physicians stated that prescription-only status for HC could be lifted under certain conditions but also some concerns, e.g., patients' safety or neglection of preventive examinations, were raised. Future research should focus on specific conditions in which extended access to HC could be agreed on.